Practical measurement for equity and justice - Takahashi, Sola; Sandoval, Carlos; Jackson, Brent; Cunningham, Jahneille; Taylor, Curtis (Frontiers in Education, 2025)
What does it mean and how does it look for practical measurement - a cornerstone of improvement science methods - to support equity and justice in schools? Practical measures are not, in themselves, a “silver bullet” that will make school systems more equitable and just, but we propose that they may support ways of reflecting on and understanding the current system that lead to shifts in organizational routines. This authors proposes 5 measurement routines that may position practical measurement as a resource for more equitable and just organizational processes. These are: (1) Attending to and reflect on day-to-day practices and processes for equity; (2) Identifying instructional moves teachers can test to advance equity; (3) Positioning students to take ownership over the learning environment; (4) Developing interpretations of how identity shapes/ is shaped the learning environment; (5) Surfacing and building on minoritized students’ strengths. These five measurement routines are examined in the context of a practical measurement development effort between WestEd and the CARE Network at the High Tech High Graduate School of Education. This collaboration led to the development of a practical measure focused on the experience of status hierarchies in math classrooms. The authors consider teachers’ uptake and use of these tools relative to the five routines of measurement for equity and justice.